2007
DOI: 10.1111/j.1365-2095.2007.00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary vitamin C on immunity, growth and survival of Indian major carp Labeo rohita, fingerlings

Abstract: An 8‐week feeding trial was conducted to evaluate the efficacy of dietary l‐ascorbic acid (AA) dosages on immunity, growth and survival of the fingerlings of Labeo rohita. AA was supplemented at 0, 100, 200 and 500 mg kg−1 basal diets. Each diet was fed for 8 weeks to duplicate groups of fingerlings of rohu with initial body weight of 35 ± 5 g. Selected biochemical and haematological analyses were evaluated every second week. At the end of the feeding trial of 56 days, fish were divided into two subgroups unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0
2

Year Published

2008
2008
2025
2025

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 52 publications
6
45
0
2
Order By: Relevance
“…For the group fed the T c (vitamin C) diet, growth (weight gain) was 22.5% higher than for controls, in agreement with the results of Misra et al (2007) who found that measures of growth such as SGR and feed conversion ratio were significantly improved when Labeo rohita fingerlings were fed a diet supplemented with vitamin C (500 mg/kg). Similar results were also obtained by various other authors for African catfish, Ictalurus punctatus (Merchie et al 1997), Asian sea bass, Lates calcarifer (Boonyaratpalin et al 1994), red sea bream, Pagrus major (Kosutarak et al 1994), Atlantic salmon, Salmo salar (Sandnes et al 1992), yellow perch, Perca flavescens (Lee and Dabrowski 2004), and pirarucu, Arapaima gigas (de Menezes et al 2006).…”
Section: Discussionsupporting
confidence: 88%
“…For the group fed the T c (vitamin C) diet, growth (weight gain) was 22.5% higher than for controls, in agreement with the results of Misra et al (2007) who found that measures of growth such as SGR and feed conversion ratio were significantly improved when Labeo rohita fingerlings were fed a diet supplemented with vitamin C (500 mg/kg). Similar results were also obtained by various other authors for African catfish, Ictalurus punctatus (Merchie et al 1997), Asian sea bass, Lates calcarifer (Boonyaratpalin et al 1994), red sea bream, Pagrus major (Kosutarak et al 1994), Atlantic salmon, Salmo salar (Sandnes et al 1992), yellow perch, Perca flavescens (Lee and Dabrowski 2004), and pirarucu, Arapaima gigas (de Menezes et al 2006).…”
Section: Discussionsupporting
confidence: 88%
“…Although some aspects of nutrition like protein, fat, carbohydrate and optimum feeding of these species have been worked out in the past, no informations are available on vitamins requirement of these commercially important fish species excepting the work on ascorbic acid requirement of C. mrigala (Mahajan and Agarwal 1980), vitamin E requirement of Labeo rohita (Sau et al 2004) and recently vitamin C of Labeo rohita (Misra et al 2007). Hence, the present study was therefore undertaken to work out dietary niacin requirement of these species.…”
Section: Introductionmentioning
confidence: 94%
“…Antioxidant vitamin C is well known for its major antistress activity (Azad et al 2007, Misra et al 2007Norouzitallab et al 2009). The antioxidant activity of ascorbic acid is based on its ability to react with free radicals.…”
Section: Discussionmentioning
confidence: 99%